Menggali Potensi Kreativitas Santri Melalui Manajemen Pendidikan Kewirausahaan di Pondok Pesantren Assuniyyah Kencong Jember - Sa’adah, Masrurotus; Ummah, Nur Ittihadatul (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
Entrepreneurship education in Islamic boarding schools (pondok pesantren) plays a strategic role in equipping students (santri) with relevant skills amidst the challenges of the global economy, particularly in addressing the persistently high unemployment rate in Indonesia, which reached 5.86% in 2023. This article explores how Pondok Pesantren Assuniyyah Kencong Jember taps into the creative potential of its students through an entrepreneurship education approach. The research employs qualitative methods to understand the dynamics of the entrepreneurship learning process. Through in-depth interviews and participatory observations, it was found that the integration of entrepreneurship education into the curriculum not only enhances technical and managerial skills but also encourages students to think creatively and innovatively in response to economic challenges. The findings indicate that a supportive environment, along with guidance from mentors and local entrepreneurs, significantly contributes to fostering an entrepreneurial spirit among the students. These findings are expected to contribute to the development of entrepreneurship education models in other Islamic boarding schools and strengthen efforts to reduce poverty through the creation of ethical and competitive new entrepreneurs.